Land acquisition and infrastructure development through land trust laws: A policy framework for Asia - Naoyuki Yoshino; Saumik Paul; Vengadeshvaran Sarma; Saloni Lakhia (Asian Development Bank Institute (ADBI), 2018)
The "land question" has invigorated agrarian studies and economic history since Marx and early 20th century writers on agrarian questions. In countries that allow private land ownership, compulsory land acquisition is the right and action of the government to take property not owned by it for public use. In the long run, growth dividends from infrastructure development and industrialization are likely to be materialized, and acquisition of land to facilitate such process remains one of the main development challenges in many Asian countries. The recent political upheaval transgressing from the industrialization drive through forcible land-grab in many parts of Asia (India, Indonesia, Nepal, and the Philippines in particular) point to the need for a sustainable policy - a framework that results in a positive sum game, benefiting the landowners without hurting the growth prospects. Combining the tools from the fields of law and economics, we propose the land trust or land lease for the development of infrastructure investment and industrialization purposes. We argue that this is one of the best ways to increase the rate of return to invite private investors into infrastructure investment. Through evidence from the success stories of land trust initiatives in many Asian countries, including India, we aim to showcase the relevance of this alternate method.
Keywords: Q15; R14; 330; land acquisition; infrastructure development; land trust laws; Asia